Social and Economic Conditions of Student Life in Europe Eurostudent VI 2016-2018 | Synopsis of Indicators - Vögtle, Eva Maria; Gwosc, Christoph (wbv Publikation, 2018)
The EUROSTUDENT project gathers data about the prevailing social and economic conditions for studying in Europe. The volume presents data and results from an up-to-date student survey conducted in 28 countries of the European Higher Education Area. The report is the most important publication of the project. The project has been implemented by researchers, data collectors, representatives of national ministries and other actors from across the whole of Europe. The project report processes a broad spectrum of information. This includes data on access to higher education, conditions for studying, international mobility of students, quality of courses and planned study programmes. The project group wants the results to stimulate educational-policy debate and to form the basis for future research work. Im Projekt EUROSTUDENT werden Daten zu den sozialen und wirtschaftlichen Rahmenbedingungen des Studierens in Europa erhoben. Der Band präsentiert die Daten und Ergebnisse einer aktuellen Studierendenbefragung in 28 Ländern des Europäischen Hochschulraums. Der Bericht ist die wichtigste Publikation des Projektes, das von Forschenden, Datensammelnden, Vertreter:innen nationaler Ministerien und anderen Akteuren aus ganz Europa umgesetzt wird. Der Projektbericht bereitet ein breites Informationsspektrum auf. Dazu gehören Daten zum Zugang zu höherer Bildung, zu Studienbedingungen, zur internationalen Mobilität der Studierenden, zur Qualität von Studiengängen und zu geplanten Studienprogrammen. Mit den Ergebnissen will die Projektgruppe bildungspolitische Debatten anregen und die Basis für künftige Forschungsarbeit legen